Medicolegal Aspects of Obstetrics — the Role of the Midwife in Hong Kong - HO, LF (Hong Kong Journal of Gynaecology, Obstetrics and Midwifery, 2023)
With the establishment of Hong Kong’s first Midwifery Clinic in 1993, midwives have taken up a direct and independent role in the delivery of obstetric care in a number of hospitals. However, the number of malpractice cases involving childbirth issues has risen dramatically in recent years. Most obstetric claims involve alleged injury to the fetus, neonate, or mother during labour and delivery. As frontline workers directly providing antenatal and intrapartum care, midwives are increasingly prone to be involved in potential medical litigation. Nurses may be accused of negligence when they fail to demonstrate reasonable and prudent behaviour in their practice. If nurses are involved in obstetric litigation, the hospital is vicariously liable for any breach of their duties by employees working within the scope of their employment. However, the courts recognise midwifery as an autonomous profession responsible for its own practice and possessing a unique body of knowledge. In the future, it is likely that the midwife may be sued as an individual defendant or co-defendant. Hong Kong midwives need to face this challenge and not only embrace wholeheartedly the concepts and practice of modern midwifery, but also demonstrate that they are in a position to discharge their duty and responsibility, to maintain their standards, and be prepared to stand up and defend this status.